The Federal Building and Hall of States (Arena Photo Post Card Co.)
One of the most beautiful and colorful building groups of the World's Fair. The Federal Building in front in 620 feet long and 300 feet wide, with a rotunda 70 feet in diameter surmounted by a 75-foot dome. Aroudn this dome is grouped three fluted columns, 150 feet high, typifying the three branches of government: legislative, executive, and judicial. Behind this building is the V-shaped Hall of States, 500 feet across at the base and with two arms 500 feet long and 140 feet wide.